2015
DOI: 10.3109/00016489.2014.990054
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in 21 patients with common cavity malformation

Abstract: The facial recess approach was used in 3 patients with CC malformation with an incomplete basal turn, and the transmastoid single-slit labyrinthotomy approach in 18 patients with classic CC malformation. After follow-up for 36 months, the average free-field hearing threshold was higher, and the scores for the CAP, SIR, IT-MAIS, and closed-set/open-set auditory speech perception tests were lower than in the control group (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
(71 reference statements)
2
20
0
Order By: Relevance
“…Xia et al [13] did follow-up for 36 months of 21 patients with common cavity deformity who underwent cochlear implantation, the average free-field hearing threshold was higher, and the scores for the CAP, SIR, IT-MAIS, and closed-set/open-set auditory speech perception tests were lower than in the control group (p \ 0.05), which is similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Xia et al [13] did follow-up for 36 months of 21 patients with common cavity deformity who underwent cochlear implantation, the average free-field hearing threshold was higher, and the scores for the CAP, SIR, IT-MAIS, and closed-set/open-set auditory speech perception tests were lower than in the control group (p \ 0.05), which is similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Six CCD CI patients were implanted using the TFRA and seven were implanted using the TSLA, as in Xia et al 15 For the TSLA, the size of the labyrinthotomy in the lateral semicircular canal was approximately 1.0 3 4.0 mm and the labyrinthotomy was sealed using temporalis fascia and muscle. To further improve outcomes for CCD CI patients, customized electrode arrays were used in patients who were implanted using the TSLA.…”
Section: Discussionmentioning
confidence: 99%
“…5 A subsequent study showed that none of 18 CCD patients implanted using the single-slit labyrinthotomy approach exhibited CSF leak or meningitis after surgery. 15 The authors speculated that the size of the labyrinthotomy has no influence on the incidence of CSF gusher, which may be associated with a defective cribriform plate in the IAC. In the single-slit labyrinthotomy approach, the labyrinthotomy and the whole cavity is sealed with temporalis fascia and muscle to stop any CSF leakage.…”
Section: Cochlear Implant Surgical Approaches For Ccd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on CCD, the modified transmastoid labyrinthotomy (lateral semicircular canal approach) was used ( Beltrame et al., 2005 , Zarandy, 2008 ). Some scholars hold the opinion that conventional facial recess approach can be used when there is a residual structure of cochlea in the area of promontory, while the modified transmastoid labyrinthotomy can be selected when the cochlea cannot be distinguished from the common cavity structure ( Xia et al., 2015 ). The electrode array was inserted successfully by the modified transmastoid labyrinthotomy approach in all CCD cases in our study.…”
Section: Discussionmentioning
confidence: 99%